Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Eva C. Sonnenschein (Science of The Total Environment, 2024)
Prymnesium parvum is a toxin-producing haptophyte that causes harmful algal blooms worldwide, which are often associated with massive fish-kills and subsequent economic losses. In here, we present nuclear and plastid genome assemblies using PacBio HiFi long reads and DNBseq short reads for the two P. parvum strains UTEX 2797 and CCMP 3037, representing producers of type A prymnesins. Our results show that the P. parvum strains have a moderate haptophyte genome size of 97.56 and 107.32 Mb. The genome assemblies present one of highest contiguous assembled contig sequences to date consisting of 463 and 362 contigs with a contig N50 of 596.99 kb and 968.39 kb for strain UTEX 2797 and CCMP 3037, respectively. The assembled contigs of UTEX 2797 and CCMP 3037 were anchored to 34 scaffolds, with a scaffold N50 of 5.35 Mb and 3.61 Mb, respectively, accounting for 93.2 % and 97.9 % of the total length. Each plastid genome comprises a circular contig. A total of 20,578 and 19,426 protein-coding genes were annotated for UTEX 2797 and CCMP 3037. The expanded gene family analysis showed that starch and sucrose metabolism, sulfur metabolism, energy metabolism and ABC transporters are involved in the evolution of P. parvum. Polyketide synthase (PKSs) genes responsible for the production of secondary metabolites such as prymnesins displayed different expression patterns under nutrient limitation. Repeat expanded and horizontal gene transfer may be two contributing factors to the high number of PKS genes found in this species. The two high quality P. parvum genomes will serve as valuable resources for ecological, genetic, and toxicological studies of haptophytes that can be used to monitor and potentially manage harmful blooms of ichthyotoxic P. parvum in the future.